Issues of Green Procurement in the Republic of Armenia (By the Example of the City of Yerevan) - Galstyan, Hamazasp; Badadyan, Gagik; Tatosyan, Kristine; Shahinyan, Mher («Տնտեսագետ» հրատ․)
Green procurement as a green financing tool is an important prerequisite for building the green economy. By implementing green procurement, it is possible to ensure a green transformation, while ensuring sustainable development sa well. Ensuring the use of green procurement in the process of green transformation of Yerevan, the capital of the Republic of Armenia, is also a vital necessity. In this case, the study of the existing situation, the raising of issues and the presentation of the proposal for the use of the appropriate tool set are derived from the imperative of the green transformation of the capital city of Yerevan. Regarding public procurement in the Republic of Armenia there is no specific system for the implementation of green procurement, and the organization of these processes is based only on voluntariness. In this case, with the analysis carried out in the given paper, an attempt was made to evaluate the situation, and also the concept of the implementation of the green procurement system was presented. Կանաչ գնումները՝ որպես կանաչ ֆինանսավորման գործիք, կանաչ տնտեսության ձևավորման կարևորագույն նախապայման են: Կանաչ գնումների իրականացմամբ հնարավորություն է ստեղծվում ապահովելու կանաչ վերափոխում՝ ապահովելով նաև կայուն զարգացում: Հայաստանի Հանրապետության մայրաքաղաք Երևանի կանաչ վերափոխման գործընթացում կանաչ գնումների կիրառման ապահովումը նույնպես անհրաժեշտություն է: Այս պարագայում առկա իրավիճակի ուսումնասիրությունը, խնդիրների վերհանումը և համապատասխան գործիքակազմի կիրառման առաջարկի ներկայացումը բխում են Երևանի կանաչ վերափոխման հրամայականից: Հայաստանի Հանրապետությունում հանրային գնումների առումով գոյություն չունի կանաչ գնումների իրականացման որոշակի համակարգ, և այդ գործընթացների կազմակերպումը հիմնված է միայն կամավորության սկզբունքի վրա: Այս պարագայում հոդվածում կատարված վերլուծությամբ փորձ է արվել գնահատելու առկա իրավիճակը, ներկայացվել է նաև կանաչ գնումների համակարգի ներդրման հայեցակարգ: Зеленые закупки как инструмент зеленого финансирования являются важной предпосылкой для становления зеленой экономики. Осуществляя зеленые закупки, можно обеспечить зеленую трансформацию, а также обеспечить устойчивое развитие. Обеспечение использования зеленых закупок в процессе зеленого преобразования Еревана, столицы Республики Армения, также является необходимостью. В данном случае изучение существующей ситуации, постановка проблем и представление предложения по использованию соответствующего инструментария вытекают из необходимости зеленой трансформации столицы Армении. В области государственных закупок Республики Армения отсутствует конкретная система осуществления зеленых закупок, и организация этих процессов осуществляется на добровольной основе. С помощью проведенного анализа, представленного в данной статье, была предпринята попытка оценить ситуацию и разработать концепцию внедрения системы зеленых закупок.
Keywords: Natural resource; Economics; Environmental Economics